Pressure drop of three-phase suspension flows (water-air-sand) in horizontal pipelines - Pironti, Filippo; Pellegrino, Gabriel; Meza, Gluber; Ramírez, Nelson (Rev. Téc. Fac. Ing. Univ. Zulia)
In this work we report experimental results and the mathematica1 model for the flow of three-phase suspensions (gas-liquid-solid) through horizontal pipes in a bench installation. Pressure drops were measured as a function of the suspension velocity and the air flow. Different salid concentrations of sand were used in harder to observe the effect of the salid upon the flow regime. The experimental results confirm what we observed in a previous work: the presence of the gas in the suspension reduced the pressure drop when there is no segregation.